Structural Analysis of F. Fitzgerald's The Great Gatsby - sabariyanto sabariyanto (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
ABSTRACTThe objectives of this research are to find out the relatedness between setting and characterization F. Scott Fitzgerald’s The Great Gatsby and to find out the relatedness between setting and plot in F. Scott Fitzgerald’s The Great Gatsby. This research used library research method and used stuctural approach. So this only focus on the intrinsic elements which build the story as a literary work, such as plot, character, and setting. The result of the research shows that structural elements of F. Fizgerald’s The Great Gatsby present a solid unity. Each element has close relation with other elements in forming the wholeness of the story. Here, there is the relatedness between setting and plot and the relatedness between plot and character in F. Fitzgerald’s The Great Gatsby.